Equatorial and low latitude ionospheric effects due to planetary wave atmospheric forcing - Chau Chong Shing, Jorge Luis (2010)
Diapositivas presentadas en First Latin American, FMT Workshop 2010, Ica, Peru, November 22- 26, 2010.